Consumer Attitude Towards Tropical Hardwoods in the United Kingdom - Mohamed, Shukri; Yacob, Mohd Rusli; Abd. Ghani, Awang Noor (Universiti Putra Malaysia Press, 1996)
A survey in United Kingdom on public attitude towards tropical timbers showed negative disposition towards tropical hardwoods and wood products. Those considering buying tropical wood products would do so if it was competitively priced, not treated with chemicals or manufactured from timber species known to them. Tropical wood products may not fare better in the future due to greater awareness of environment quality. The survey results revealed that males and those from higher incomes groups unlike the others were willing to purchase tropical hardwood, especially if it was from substainable forests.